A Historical Lens on Organisational Justice:Evolution, Perspectives, and Implications (Maharaja Surajmal Institute Law Journal, 2026)
Fairness perceptions in the workplace have long been recognized as a cen tral determinant of employee motivation, performance, and organizational  harmony. Organizational justice refers to employees’ subjective assessments  of fairness concerning outcomes, procedures, and interpersonal treatment.  This paper provides a historical and conceptual analysis of the evolution of  organizational justice, tracing its development from early notions of rela tive deprivation (Stouffer et al., 1949) to contemporary, multidimensional  frameworks. The review identifies three major intellectual phases—dis tributive, procedural, and interactional justice—and examines how each  stream has cumulatively shaped the field. The paper highlights the interplay  among these perspectives and underscores the integrative movement that  positions justice as a multifaceted construct influencing employee attitudes  and behaviors across organizational contexts.
Keywords: Organizational justice; dis tributive justice; procedural justice; inter actional justice; equity; fairness